ANFIS Modelling of Flexible Plate Structure - Al-Khafaji, A. A. M.; Darus, I. Z. Mat; Jamid, M. F. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
This paper presented an investigation into the performance of system identification using an Adaptive Neuro-Fuzzy Inference System (ANFIS) technique for the dynamic modelling of a two- dimensional flexible plate structure. It is confirmed experimentally, using National Instrumentation (NI) Data Acquisition System (DAQ) and flexible plate test rig that ANFIS can be effectively used for modelling the system with highly accurate results. The accuracy of the modelling results is demonstrated through validation tests including training and test validation and correlation tests.